The Effect Of Erythropoietin Administration In Experimental Burns Wound Healing: An Animal Study - Sandhi, Afriyanti; Wardhana, Aditya (Lingkar Studi Bedah Plastik Foundation, 2016)
Background: The hematopoietic growth factor erythropoietin (EPO) attracts attention due to its all-tissue-protective pleiotropic properties. The purpose of this study is to investigate the effect of EPO in experimental burn wounds healing. Methods: Fifteen healthy Sprague-Dawley, strain of Rattus Novergicus weighing 300-350 grams, were prepared to achieve deep dermal burns. Animals were randomized to receive either low-dose EPO injection (600 IU/mL), high-dose EPO injection (3000 IU/mL) or nothing (control group). After 14 days of observations, quantitative and qualitative assessments of wound healing was determined. Results: The size of the wound area and re-epithelialization rate percentage was determined on Day-0, Day-5, Day-10, and Day-14. The average of raw surface areas measurement (p value: 0.012 in day-5; 0.009 in day-10 and 0.000 in day-14) and healing percentage of the lesions (p value: 0.011 in day-5; 0.016 in day-10 and 0.010 in day-14) were significantly best in the low-dose EPO grup compared to the control group and high-dose EPO grup. The histopathology evaluation revealed that the highest score for for re-epithelialization, granulation tissue and neo-angiogenesis were achieved by the low-dose EPO injection group than in both control and high-dose EPO injection groups. Conclusion: In this animal study using Sprague-Dawley rats, Recombinant Human EPO (rHuEPO) injection administration prompted the evidences of improved re-epithelialization and wound healing process of the skin caused by deep dermal burns. These findings may lead to a new therapeutic approach to improve the clinical outcomes for the management of burns wound healing.